Non-Pharmacological Pain Management: The Role of Nurse Guided Back Massage for Low Back Ache - Badhe, Archana M.; Gurjar, Nema Ram; Sonawane, Dhiraj V.; Mane, Dhiraj kumar (Journal of Neonatal Surgery, 2025)
Background: Men and women are equally affected by low back pain (LBP), which can range in intensity from a dull, constant ache to a sudden, sharp sensation that hinders the person. Intrusive procedures are more likely to cause adverse outcomes in older adults, which emphasizes the value of non-pharmacologic and non-invasive therapy for individual requirements. In light of concerns about the overuse of medications and the potential for opioid dependence, there is growing interest in non-pharmacological approaches to pain management. Nurses play a vital role in giving different interventions to treat back pain effectively. This study aims to study the role of nurse guided back massages on LBP among patients attending the outpatient department (OPD) in selected hospitals. Materials and Methods: A quasi-experimental, one-group pretest–posttest time series research design was used to conduct a study among the patients attending OPD in selected hospitals. A total of 160 respondents were studied from October 2021 to February 2022. A numerical pain scale and a semi-structured self- administered questionnaire were used to collect data. Only respondents who gave informed consent were issued the questionnaire to complete at their convenience. Back massages were given for 6 weeks, thrice a day in a week for 20 min regularly. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 24.0. Descriptive data were presented in the form of bar graphs and frequency tables. Results: The study showed that 56.25% of the respondents had severe LBP in the pretest. After doing selected physical exercises, the severe pain level reduced to 50% in Post-test 1, 21.88% in Post-test 2, and 8.75%in post-test-3. The t value of the difference in mean reduction of LBP was tabulated, and the calculated t values were (1.15, 6.94, 10.12) statistically significant at 0.05 level of significance (P < 0.05). Conclusion: LBP is seen as an issue for all ages and all sectors of society. One common component of pain treatment programs focuses on increased physical exercise reconditioning, and exercise would increase strength and concomitantly decrease pain as a long-term effect. The investigator found that physical activities were very effective and beneficial in reducing back pain among patients with LBP.